Association between self-rated health and mortality: 10 years follow-up to the Pró-Saúde cohort study - Nery Guimarães Joanna; Chor Dóra; Werneck Guilherme; Carvalho Marilia; Coeli Claudia; Lopes Claudia S; Faerstein Eduardo (BMC, 2012)
Abstract Background The association between self-rated health (SRH) and mortality is well documented in the literature, but studies on the subject among young adults in Latin America are rare, as are those evaluating this association using repeated SRH measures, beyond the baseline measurement. This study aims to evaluate the association between SRH evaluated at three data collection stages and mortality. Methods Cox regression models were used to examine the association between SRH (Very good, Good, Fair/Poor) varying over time and mortality, over a 10 year period, in a cohort of non-faculty civil servants at a public university in Rio de Janeiro, Brazil (Pró-Saúde Study, n = 4009, men = 44.4%). Results About 40% of the population changed their self-rating over the course of follow-up. After adjustment for self-reported physician-diagnosed chronic diseases and other covariates, men who reported "Fair/Poor" SRH showed relative hazard of death of 2.13 (CI95% 1.03-4.40) and women, 3.43 (CI95% 1.23-9.59), as compared with those who reported "Very good" SRH. Conclusions In a population of young adults, our findings reinforce the role of SRH as a predictor of mortality, even controlling for objective measures of health.